Structural insight into the unique dsDNA binding topology of the human ORC2 wing helix domain. (19th April 2019) - Zhang, Jiahai; Guo, Qiong; Gao, Jun; Xu, Chao; Zhang, Beibei; Li, Mingwei; She, Jiaqi; Shi, Yunyu; Zhang, Zhiyong; Ruan, Ke; Wu, Jihui
Abstract : The origin recognition complex (ORC) is indispensable for the initiation of DNA replication during the cell cycle. The DNA‐binding modes of the human ORC winged helix domain (WHD) remain enigmatic, as the dsDNA recognition sites of archaeal and Saccharomyces cerevisiae ORC WHDs are distinct. Here, we solved the high‐resolution crystal structure of the human ORC2 WHD, although its complex with dsDNA is difficult to crystallize due to its weak binding affinities. The near‐complete NMR backbone assignments and chemical shift perturbations reveal a new dsDNA binding topology in addition to the conserved β‐sheet hairpin region, in which residues show higher dynamics. The key interacting residues (R540, K548, and K549) were validated by mutagenesis studies. Our data suggest that the ORC2 WHD recognizes dsDNA sequences through its flexible β‐sheet hairpin as an anchor point, while the rest of the protein adopts various orientations in different species. This weak but real interaction module identified by NMR is useful for the structural reconstruction of large biomolecular complexes using cryo‐EM. The binding topology and dynamics of ORC2 WHDs were also underpinned by molecular dynamics simulations. Abstract : Zhang et al . solved the high‐resolution crystal structure of human origin recognition complex subunit 2 wing helix domain. NMR studies further reveal that this domain recognizes dsDNA through the conserved flexible β‐sheet hairpin as an anchor point, while the rest of the protein adopts various orientations in different species, as also underpinned by molecular dynamics simulations.